2020
DOI: 10.1186/s13173-020-00097-0
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of two computer science degree offerings

Abstract: This article presents an in-depth analysis and comparison of two computer science degree offerings, viz., the Bologna BSc in Information Systems and Computer Engineering, offered by the Instituto Superior Técnico of the University of Lisbon, Portugal, and the BSc in Computer Science offered by the Pontifical Catholic University of Rio de Janeiro, Brazil. The analysis is based on the student transcripts collected from the academic systems of both institutions over circa one decade. The article starts with a des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The professionals are at diverse levels for working in different occupations [8]. During the disclosure of computer science simultaneously, various problems arise from computer technology and produce scientific units systematically, each specifically referred to as a unit of lecture material from a curriculum [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…The professionals are at diverse levels for working in different occupations [8]. During the disclosure of computer science simultaneously, various problems arise from computer technology and produce scientific units systematically, each specifically referred to as a unit of lecture material from a curriculum [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [15][16][17][18] found that factors that may significantly influence customers' purchasing decisions include shelf space allocation and layout display. Personal or social factors may also influence the urge to purchase another product, a phenomenon that has been studied via Market Basket Analysis [19][20][21][22][23][24][25], which analyzes the correlation of products that customers are most likely to buy at the same time [26][27][28]. The management of shelf space was found to be a problem affecting consumers' purchasing behaviors; the effectiveness of shelf layouts between nearby supermarkets was compared to investigate how to increase profits and improve customer satisfaction [29][30][31].…”
Section: Introductionmentioning
confidence: 99%